High dose sequential chemotherapy with autologous transplantation versus dose-dense chemotherapy MegaCEOP as first line treatment in poor-prognosis diffuse large cell lymphoma: an "Intergruppo Italiano Linfomi" randomized trial - U Vitolo; AM Liberati; MG Cabras; M Federico; E Angelucci; L Baldini; C Boccomini; M Brugiatelli; R Calvi; G Ciccone; A Genua; GL Deliliers; et al. (Haematologica, 2005)
BACKGROUND AND OBJECTIVES: Poor prognosis diffuse large cell lymphoma (DLCL) responds poorly to standard chemotherapy. Randomized studies comparing high-dose chemotherapy with autologous stem-cell transplantation (ASCT) against standard chemotherapy have produced conflicting results. Dose-dense chemotherapy with granulocyte colony-stimulating factor (G-CSF) support seems to hold promise. The purpose of this multicenter, randomized trial was to compare failure-free and overall survival in patients with poor prognosis DLCL treated with high-dose sequential (HDS) chemotherapy followed by ASCT or an outpatient dose-dense chemotherapy regimen (MegaCEOP). DESIGN AND METHODS: Between 1996 and 2001, 130 DLCL patients, aged < or = 60 years, with intermediate-high or high-risk disease, according to the International Prognostic Index score, and/or bone marrow involvement were enrolled. Sixty were randomized to HDS chemotherapy plus high-dose mitoxantrone and melphalan with ASCT (arm A) and 66 to the MegaCEOP regimen (6-8 courses of an escalated dose of cyclophosphamide and epirubicin plus vincristine and prednisone with G-CSF every 2-weeks) (arm B); 4 patients were considered ineligible. RESULTS: The complete remission rate was 59% in arm A and 70% in arm B (p = 0.18). After a median follow-up of 78 months, the 6-year failure-free survival was 45% in arm A and 48% in arm B (hazard ratio = 1.15, 95% confidence intervals = 0.72-1.84, p = 0.56). The 5-year overall survival was 49% in arm A and 63% in arm B (hazard ratio = 1.67, 95% confidence interval = 0.98-2.85, p = 0.06). Two cases of secondary acute myeloid leukemia were observed after treatment in group A. INTERPRETATION AND CONCLUSIONS: HDS and ASCT as initial therapy for patients with poor-prognosis DLCL does not provide a benefit over that of outpatient dose-dense MegaCEOP chemotherapy.